Nonauditory Functions in Low-performing Adult Cochlear Implant Users. Issue 5 (June 2021) - Völter, Christiane; Oberländer, Kirsten; Carroll, Rebecca; Dazert, Stefan; Lentz, Benjamin; Martin, Rainer; Thomas, Jan Peter
Abstract : Introduction: Despite substantial benefits of cochlear implantation (CI) there is a high variability in speech recognition, the reasons for which are not fully understood. Especially the group of low-performing CI users is under-researched. Because of limited perceptual quality, top-down mechanisms play an important role in decoding the speech signal transmitted by the CI. Thereby, differences in cognitive functioning and linguistic skills may explain speech outcome in these CI subjects. Material and Methods: Fifteen post-lingually deaf CI recipients with a maximum speech perception of 30% in the Freiburger monosyllabic test (low performer = LP) underwent visually presented neurocognitive and linguistic test batteries assessing attention, memory, inhibition, working memory, lexical access, phonological input as well as automatic naming. Nineteen high performer (HP) with a speech perception of more than 70% were included as a control. Pairwise comparison of the two extreme groups and discrimination analysis were carried out. Results: Significant differences were found between LP and HP in phonological input lexicon and word retrieval ( p  = 0.0039 ** ). HP were faster in lexical access ( p  = 0.017 * ) and distinguished more reliably between non-existing and existing words ( p  = 0.0021 ** ). Furthermore, HP outperformed LP in neurocognitive subtests, most prominently in attention ( p  = 0.003 ** ). LP and HP were primarily discriminated by linguistic performance and to a smaller extent by cognitive functioning (canonic r  = 0.68, p  = 0.0075). Poor rapid automatic naming of numbers helped to discriminate LP from HP CI users 91.7% of the time. Conclusion: Severe phonologically based deficits in fast automatic speech processing contribute significantly to distinguish LP from HP CI users. Cognitive functions might partially help to overcome these difficulties.